Ribozyme-Mediated Downregulation Uncovers DNA Integrity Scanning Protein A (DisA) as a Solventogenesis Determinant in Clostridium beijerinckii - Ujor, Victor Chinomso; Lai, Lien B.; Okonkwo, Christopher Chukwudi; Gopalan, Venkat; Ezeji, Thaddeus Chukwuemeka (Frontiers in Bioengineering and Biotechnology, 2021)
Carbon catabolite repression (CCR) limits microbial utilization of lignocellulose-derived pentoses. To relieve CCR in Clostridium beijerinckii NCIMB 8052, we sought to downregulate catabolite control protein A (CcpA) using the M1GS ribozyme technology. A CcpA-specific ribozyme was constructed by tethering the catalytic subunit of Escherichia coli RNase P (M1 RNA) to a guide sequence (GS) targeting CcpA mRNA (M1GSCcpA). As negative controls, the ribozyme M1GSCcpA-Sc (constructed with a scrambled GSCcpA) or the empty plasmid pMTL500E were used. With a ~3-fold knockdown of CcpA mRNA in C. beijerinckii expressing M1GSCcpA (C. beijerinckii_M1GSCcpA) relative to both controls, a modest enhancement in mixed-sugar utilization and solvent production was achieved. Unexpectedly, C. beijerinckii_M1GSCcpA-Sc produced 50% more solvent than C. beijerinckii_pMTL500E grown on glucose + arabinose. Sequence complementarity (albeit suboptimal) suggested that M1GSCcpA-Sc could target the mRNA encoding DNA integrity scanning protein A (DisA), an expectation that was confirmed by a 53-fold knockdown in DisA mRNA levels. Therefore, M1GSCcpA-Sc was renamed M1GSDisA. Compared to C. beijerinckii_M1GSCcpA and _pMTL500E, C. beijerinckii_M1GSDisA exhibited a 7-fold decrease in the intracellular c-di-AMP level after 24 h of growth and a near-complete loss of viability upon exposure to DNA-damaging antibiotics. Alterations in c-di-AMP-mediated signaling and cell cycling likely culminate in a sporulation delay and the solvent production gains observed in C. beijerinckii_M1GSDisA. Successful knockdown of the CcpA and DisA mRNAs demonstrate the feasibility of using M1GS technology as a metabolic engineering tool for increasing butanol production in C. beijerinckii.